Typical Values of the Nguyen Dynasty’s Decorative Art on Bronze Objects in Hue - Phan Le Chung; Nguyen Thi Hien Le (Journal La Sociale, 2022)
In the general relationship of culture and art, the Nguyen lords and kings made many contributions to the shaping and development of Cochinchina, enhanced the country's position and influence with other countries in the region. The decorative art on bronze objects in the Nguyen Dynasty contains many cultural, historical and aesthetic values with multi-dimensional and multi-layered symbol. This has shown the synthesis of values, in which aesthetic value is one of the outstanding points. The decorative art on bronze objects in the Nguyen Dynasty take an important role in preserving and conserving national artistic and cultural values. Besides this, the expressive value on bronze and the emotiveness from the surface of the material also enhance the values of the decorative art. The Nguyen Dynasty’s decorative art on bronze objects in Hue has shown the richness of art and culture. Through the study we can see and feel the great ingenuity and creative spirit of the artisan classes. This is one of the factors affirming the position of the Nguyen dynasty's decorative art on bronze objects in the general of Vietnamese bronze art.